THE ALLEGED EXTREMISM OF THE TALIBAN AND ITS RELATION WITH THE HANAFITE JURISPRUDENCE - Meirison Meirison (Jurnal AL-AHKAM, 2021)
In the fall of 1994, a group calling itself the Taliban endorsed Afghanistan from what it called warlords and criminals. Is that assumption correct? They were seeking to establish an Islamic government according to their interpretation of Sharia. Most Taliban leaders were Mujahideen, while the soldiers were Afghan refugees studying in Pakistani religious schools. The schools are run by the Pakistan Muslim Scholars Association, the conservative wing of the religious, political party, led by Maulana Fazlur Rahman Grim Qazi Hussain Ahmed, the Jamaat al-Islam party leader. Supporter of the Mujahideen. In the discussion of this article, we conducted a literature study and a descriptive-analytical approach   after   reviewing   all   the   available   literature   and   starting   with collecting data holistically and then verifying and analyzing the data, after that, we tried to interpret the relationship between the attitude of the Taliban and the Hanafi school, which is considered to make the Taliban radical. After examining the existing groups and schools, the Hanafi school is not entirely responsible for the extremes of the Taliban because there are also Shia and Ismaili schools that are known to be violent and radical. Even in the past, the Shi'ite Ismaili school acted as assassins and spreaders of terror and killed the rulers. At the same time, the other group is Ahmadiyah and several other Islamic splinter groups.